Members of legal relationships of polygraph checking - Shevchenko, Serhii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2019)
In the article the author investigates the relations that arise during conducting polygraph checking in state authorities. The author identifies the main subjects of legal structure of administrative legal relations carrying out polygraph interview. Among other things, the author analyzes the terms used in the administrative attitude of polygraph checking and identifies some deficiencies of normative regulation. According to the results of the study, is substantiated that lack of regulation does not allow reflect the managerial influence onpolygraph checking relations in administrative law.The subjects of administrative relations for conducting polygraph surveys are the actual holders of the rights, duties and powers in the sphere of providing the functions of public authority, which are accompanied by the receipt of indicative information with the use of a special technical means - a computer polygraph.Legislative unregulation of relations on conducting psychophysiological surveys with the use of polygraph determines the systemic errors and the hopelessness of departmental norm designing.Summarizing the terminology, it can be noted that the rule-maker mostly determines not the intrinsic features of the parties of the polygraphic relations, but rather, the compliance with the criteria for the persons who are testing and interviewed. In most cases, two categories of subjects are interviewed: candidates for the department and current employees. The obligatory requirement for the respondent is to provide voluntary consent (without emphasizing the written form) and the absence of medical contraindications.